Pay for performance and hip fracture outcomes: an interrupted time series and difference-in-differences analysis in England and Scotland. (August 2019) - Metcalfe, D.; Zogg, C. K.; Judge, A.; Perry, D. C.; Gabbe, B.; Willett, K.; Costa, M. L.
Abstract : Aims: Hip fractures are associated with high morbidity, mortality, and costs. One strategy for improving outcomes is to incentivize hospitals to provide better quality of care. We aimed to determine whether a pay-for-performance initiative affected hip fracture outcomes in England by using Scotland, which did not participate in the scheme, as a control. Materials and Methods: We undertook an interrupted time series study with data from all patients aged more than 60 years with a hip fracture in England (2000 to 2018) using the Hospital Episode Statistics Admitted Patient Care (HES APC) data set linked to national death registrations. Difference-in-differences (DID) analysis incorporating equivalent data from the Scottish Morbidity Record was used to control for secular trends. The outcomes were 30-day and 365-day mortality, 30-day re-admission, time to operation, and acute length of stay. Results: There were 1 037 860 patients with a hip fracture in England and 116 594 in Scotland. Both 30-day (DID -1.7%; 95% confidence interval (CI) -2.0 to -1.2) and 365-day (-1.9%; 95% CI -2.5 to -1.3) mortality fell in England post-intervention when compared with outcomes in Scotland. There were 7600 fewer deaths between 2010 and 2016 that could be attributed to interventions driven by pay-for-performance. A pre-existing annual trend towards increased 30-day re-admissions in England was halted post-intervention. Significant reductions were observed in the time to operation and length of stay. Conclusion: This study provides evidence that a pay-for-performance programme improved the outcomes after a hip fracture in England. Cite this article: Bone Joint J 2019;101-B:1015–1023.